Organoleptic Analysis Of Three Types Of Watermelon On The Quality Of Jam - Pulungan, Dzaky Hilmy; Anggraini, Ezi; Faridah, Anni; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Jam is a popular fruit-based product due to its sweet flavor, distinctive aroma, and smooth texture, while watermelon has great potential as a jam ingredient because of its abundant availability in Indonesia and its high water, sugar, and lycopene content. This study aimed to determine the effect of three types of watermelon Inul watermelon (X1), seedless red watermelon (X2), and striped red watermelon (X3) on the quality of watermelon jam based on sensory and hedonic evaluations. Thirty panelists participated in three replications to assess four main parameters: color, aroma, texture, and taste. The sensory test results showed that jam made from seedless red watermelon (X2) had the best quality with color score 5.74, aroma 6.14, texture 5.69, and taste 6.22. Meanwhile, the hedonic test results revealed that the same sample (X2) was most preferred by panelists, with color score 5.89, aroma 5.53, texture 5.90, and taste 5.60. Analysis of variance indicated significant differences in color, texture, and taste, but no significant difference in aroma. Therefore, it can be concluded that watermelon type influences both the quality and acceptability of watermelon jam, with seedless red watermelon (X2) producing the best jam characterized by a bright red color, fresh aroma, soft texture, and balanced natural sweetness.